Stress relief? Funding structures and resilience to the Covid shock - Kristin Forbes; Christian Friedrich; Dennis Reinhardt (Bank of Canada, 2023)
This paper explores whether different funding structures-including the source, instrument, currency, and counterparty location of funding-affected the extent of financial stress experienced in various countries and sectors during the Covid-19 spread in early 2020. We measure financial stress using a new dataset on changes in credit default swap spreads for sovereigns, banks, and corporates. Then we use country-sector and country-sector-time panels to assess if these different funding structures mitigated-or amplified-the impact of this risk- off shock. A higher share of funding from non-bank financial institutions (NBFI) or in US dollars was correlated with significantly greater stress, while a higher share of funding in debt instruments (instead of loans) or cross-border (instead of domestic) did not significantly impact resilience. The results suggest that macroprudential regulations should broaden their current focus to take into account exposures to NBFI and dollar funding, giving less priority to regulations focused on residency (i.e., capital controls). After the sharp increase in financial stress in early 2020, policy responses targeting these structural vulnerabilities (i.e., US swap lines and policies focused on NBFIs) were more effective at mitigating stress related to these funding structures than policies supporting banks, even after controlling for macroeconomic policy responses.
Keywords: E44; E65; F31; F36; F42; G18; G23; G38; 330; Coronavirus disease (COVID-19); Exchange rates; International topics; Financial institutions; Financial stability; Financial system regulation and policies; Coronavirus; Finanzkrise; Finanzierung; Informeller Finanzsektor; Kreditderivat; Geldpolitik; Finanzmarktaufsicht; US-Dollar; Welt